The Acts of the Apostles: What Really Happened in the Earliest Days of the Church. By Gerd Lüdemann, assisted by Tom Hall - Gregory, Andrew F. (The journal of theological studies, 2008)
This book is a revised and restructured version of Lüdemann's earlier work, Early Christianity According to the Tradition in Acts: A Commentary (SCM/Fortress, 1989), which was itself an English translation of Das frühe Christentum nach den Traditionen der Apostelgeschichte: Ein Kommentar (Vandenhoeck & Ruprecht, 1987). It is written for a wider audience than its predecessor so it therefore complements rather than supersedes the earlier version and will be a useful tool for students. There is less engagement with secondary sources, less technical exegesis of Acts, and more space is given to setting out Lüdemann's assessment of what we may know about Primitive Christianity (his preferred term) on the basis of Acts and the authentic letters of Paul.